Estudio Ergonómico de los puestos de trabajo con PVD (Pantallas de Visualización de Datos) del Área Administrativa de HIDROAGOYAN CELEC E.P - Hernández Ugsiña, Gissela Abigail (2019)
The use of the display screens are common within the work environment, since they are part to perform a task, which is why this research aimed to apply an ergonomic study of the workplaces with PVD (data display screens ) of the administrative area of Hidroagoyán CELEC EP to generate comfort. Different hazards associated with the use of PVD in workers of the administrative area of Hidroagoyán CELEC E.P were identified and the associated risks were determined, in this way the workers were ergonomically evaluated. Methodologically, a non-experimental design was used as it did not manipulate the study variables, the type of study was descriptive, deductive, inductive and field; The application of the Rula method and the Lest method, allowed the following results to be obtained that 20% of the workers do not have adequate equipment in the work station causing ergonomic risks, while with the Lest method it was possible to observe 75% have weak discomfort In a 15% average discomfort, 10% strong discomfort and 0% harmful situation, evidencing that all workers need to make active daily breaks, reaching the conclusion that by staying in front of the computers in an incorrect way, it physically affects the workers , presenting spinal injuries when having a bad position in front of the computer or PVD.